Evaluasi Tingkat Pengetahuan Pasien terhadap Beyond Use Date di Puskesmas Purwokerto Utara I - Sunarti Sunarti; Intan Rovenalia Muzaeri; Nur Khusna Yuniatri; Nurhandini Hanurata Khoirunnisa; Ine Febrianti; Jennie Christiani; Jeri Alfa Rozi (Universitas Muhamadiyah Manado, 2026)
Introduction: The Beyond Use Date (BUD) is the expiration date for a drug product after its primary packaging has been opened, mixed, or prepared. The BUD differs from the expiration date printed on the manufacturer's packaging and is not always listed on the drug, so many people still don't fully understand this concept.Objective: To evaluate the level of knowledge of Prolanis patients regarding the Beyond Use Date (BUD) at the Purwokerto Utara I Community Health Center before and after being given counseling. Methods: A quantitative descriptive method with a cross-sectional design was used on 20 Prolanis patient respondents. Primary data collection consisted of questionnaires administered before (pretest) and after (posttest) the lecture-based counseling using flyers. Data analysis was performed using univariate analysis. Results: The level of knowledge of Prolanis patients regarding Beyond Use Date before counseling showed that the majority were in the poor category with 16 respondents (80.0%) and the sufficient category with 4 respondents (20.0%). After being given counseling, there was an increase in the good category with 6 respondents (30.0%), but the majority were still in the poor category with 14 respondents (70.0%).Conclusion: The level of knowledge of Prolanis patients regarding Beyond Use Date (BUD) at Purwokerto Utara I Health Center before counseling was mostly in the poor category, and after counseling there was an increase although most were still in the poor category.